Problematika Pemerolehan Bahasa Arab pada Santri berkepribadian Ekstrovert dan Introvert - Hamid, Tb. Abdul; Kosim, Abdul; Azhar, Mohd. (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2024)
Learning and getting used to Arabic at the Daarul Ma'arif Islamic Boarding School in Pasawahan Purwakarta is characterized by prominent differences in the introverted and extroverted personalities of the students. These differences directly or indirectly influence their achievements in acquiring Arabic language skills. This research aims to identify the personalities of students between introverts and extroverts, then find out their impact on the acquisition of Arabic, as well as the problems faced by both. The research method used is descriptive qualitative with data collection steps namely observation, interviews, questionnaires and documentation. The results obtained from this research are that students with introverted personalities experience obstacles in acquiring Arabic due to very high levels of shyness resulting in difficulties in practicing Arabic directly, this is also influenced by their lack of social interaction so that their mastery and experience of vocabulary not fulfilled well. Students with extroverted personalities also experience problems in language acquisition, they are hampered by mastering vocabulary and also understanding and mastering Arabic language rules.